Scrape-off layer density tailoring with local gas puffing to maximize ICRF power coupling in ITER. (May 2019) - Zhang, W.; Bilato, R.; Lunt, T.; Messiaen, A.; Pitts, R.A.; Lisgo, S.; Bonnin, X.; Bobkov, V.; Coster, D.; Feng, Y.; Jacquet, P.; Noterdaeme, JM.
Highlights: First study of gas puff effects on SOL density and ICRF coupling in ITER. Midplane designed gas puffing increases the coupling resistance by ∼150−200% for both ICRF antennas. Outer top gas puffing increases the coupling resistance by ∼100−150% for one antenna and by ∼30−60% for the other antenna. To maximize ICRF coupling in ITER, the fueling gas should be injected as close as possible to the ICRF antenna locations with the gas cloud covering the antennas. Abstract: The coupling of ion cyclotron range of frequencies (ICRF) power to the plasma depends critically on the scrape-off layer (SOL) density since the fast wave is evanescent below the cut-off density. The ICRF power coupling can be improved by increasing the SOL density locally in front of the antenna by means of local gas puffing/fueling. To understand the influence of local gas puffing on the SOL and ICRF coupling and to find the optimized gas valve positions to maximize ICRF coupling in ITER, the 3D SOL code EMC3-EIRENE is used to calculate the SOL density, and the ICRF antenna codes ANTITER and FELICE are then used to calculate the coupling resistances. Purely deuterium plasma is simulated and the total gas puff rate for all studied cases is 4.5e22 el/s. The divertor gas puffing case is considered as the reference case. The density and temperature profiles in the reference case are well fitted to the standard ITER profiles (both for the low and medium density) with proper transport parameter profiles. The gas source is then switched to other local positions of the main chamber while all other simulation parameters are kept the same. The simulation results indicate that midplane gas puffing increases the antenna coupling resistance most significantly (by 150%-200%) for both ICRF antennas. This increase is at the same level as long as the gas valve is located toroidally close to the antenna, no matter if the gas valve is right to or left to the antenna. Outer top gas puffing increases the coupling resistance less significantly (by 100%–150%) for the antenna with good magnetic field line connections to the gas valve, but the increase is at a much smaller level (by ∼30%–60%) for the other antenna with only partial field line connections to the valve. The simulations thus confirm for ITER a behavior similar as seen experimentally in current devices and strongly suggest that ITER should modify the existing main chamber injection configuration to bring one of the four planned injection points closer to the antennas.